PENGARUH ASIMETRI INFORMASI DAN UKURAN PERUSAHAAN TERHADAP PRAKTIK MANAJEMEN LABA (STUDI KASUS PADA PERUSAHAAN RIGHT ISSUE PERIODE 2010– 2015) - Oktaviani, Yolanda B1031131009 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
The term earnings management emerged as a direct consequence of the efforts of managers or preparers of financial statements to perform management accounting information, particularly income (earnings), for the sake of personal and/or company. Earnings management can not be interpreted as a negative action since it does not profit-oriented management of earnings manipulation. Theoretically, there are many ways or methods that may be taken by the managers (preparers of financial statements) to affect reported earnings. In this study,management profit is measured by calculating the discretinary accruals. Asymmetry of informastion measured using bid-ask spreads and the size of the company measured using total assets. The population of this research is the company that does the right issue listed on the Indonesia stock exchange. The samples obtained by puposive sampling techiques and obtained samples of the end of as many as 50 companies who do the non financial right issue in 2010-2015. Based on the result of hypothesis testing using multiple linear analysis method in this  research. Then the obtained conlusions partially that the asymmetry of information has no effect significant and negatively to earnings management, while the size of the company’s significant and influential negatively to earnings management. As well as testing simultaneosly obtained the conclusion that the assymetry of information and the size of the company’s significant and nfluential negatively to earnings management onthe company that does the right issue listed on the Indonesia stock exchange of the year 2010-2015. Keywords: Earnings management,  the asymmetry of information, the size of the company.